Future Changes in Winter‐Time Extratropical Cyclones Over South Africa From CORDEX‐CORE Simulations - Sandeep Chinta; C. Adam Schlosser; Xiang Gao; Kevin Hodges (Earth's Future)
Abstract Extratropical cyclones (ETCs) significantly impact mid‐latitude weather patterns and are crucial for understanding the societal implications of regional climate variability, climate change, and associated extreme weather. In this study, we examine the projected future changes in winter‐time ETCs over South Africa (SA) using simulations from CORDEX‐CORE Africa. We utilized three regional climate models, each driven by three different global climate models that simulate both the current climate and a future climate experiencing strong human‐induced warming. From these, we assess changes in ETC frequency, track density, intensity, storm severity, and associated rainfall. The results indicate a significant reduction in the aggregate ETC frequency and track density, although track density is projected to increase prominently along the western coastal regions. Models show mixed trends in cyclone intensity projections, but overall results indicate weaker future cyclones, with reduced peak relative vorticity and increased minimum sea level pressure. Examining the Meteorological Storm Severity Index reveals notable regional variations in future storm severity. Average rainfall associated with ETCs is projected to decrease across SA, especially around Cape Town, highlighting a potential shift in the spatial distribution of rainfall with substantial consequences for water supply. We further investigated extreme ETCs (EETCs) and found that the trends for EETCs are generally similar to those for ETCs, with a notable decrease in frequency and regional variations in storm severity. These findings underscore the importance of developing targeted adaptation strategies to address the projected impacts of future ETCs on SA's climate and communities.